Sikap Kerja Duduk-Berdiri Bergantian Menurunkan Kelelahan, Keluhan Muskuloskeletal Serta Meningkatkan Produktivitas Kerja Penyetrika Wanita di Rumah Tangga - I Made Krisna Dinata; Nyoman Adiputra; I Putu Gede Adiatmika (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2015)
Many routine activities undertaken in the household are repeated every day throughout the year so can potentially cause health problems if not applied theprinciples of ergonomics. From the survey and measurement of domestic workers in several places in Denpasar, we found that the most complained was the process of ironing so it’s a priority to look for a solution. That complaints arise because the process of ironing is in static and monotony position. In addressing this issue , we need a change in attitude of working so that static work posture can be avoided. The use of specially designed chairs can make workers to work with a dynamic working attitude that is alternating sitting-standing posture.This experimental study using teatment by subject design with two periodeintervension  that sitting posture  and alternating sitting-standing  posture. The number of samples studied were 9 people using simple random  sampling technique. The study was conducted in a place that has been designed such as a simulation. Data collection was conducted over three days to sitting posture and three days to alternating sitting-standing posture at 8:00 to 17:00 pm divided into three sessions.In the assessment of workload showed a decrease of 19.72 % working pulse and the reduction of %CVL was 19.80%. Musculoskeletal complaints fell by 13.15%. Pain in the waist and buttocks most complained at work sitting posture (waist 37.04%; buttocks 33.33% ). For fatigue assessment using Bourdon Wiersma Questionnaires obtained 11.79% increase in speed, 42.68% in accuracy, and 13.21% in constancy. There was an increase in productivity by 38.46%, which is associated with reduced workload and duration of work. After statistical tests, obtained all the change that occur significant (p<0.05). Working-time graph showed that workers could work for eight hours continuously.It can be concluded that alternating sitting-standing posture can reduce workload, fatigue,  and musculoskeletal complaints, as well as increase productivity iron women in the household. The results of this research can be used to improve the quality of life of the worker in household.